Answer:
y have 3K
xD
Step-by-step explanation:
<span>Simplifying
7(2e + -1) + -3 = 6 + 6e
Reorder the terms:
7(-1 + 2e) + -3 = 6 + 6e
(-1 * 7 + 2e * 7) + -3 = 6 + 6e
(-7 + 14e) + -3 = 6 + 6e
Reorder the terms:
-7 + -3 + 14e = 6 + 6e
Combine like terms: -7 + -3 = -10
-10 + 14e = 6 + 6e
Solving
-10 + 14e = 6 + 6e
Solving for variable 'e'.
Move all terms containing e to the left, all other terms to the right.
Add '-6e' to each side of the equation.
-10 + 14e + -6e = 6 + 6e + -6e
Combine like terms: 14e + -6e = 8e
-10 + 8e = 6 + 6e + -6e
Combine like terms: 6e + -6e = 0
-10 + 8e = 6 + 0
-10 + 8e = 6
Add '10' to each side of the equation.
-10 + 10 + 8e = 6 + 10
Combine like terms: -10 + 10 = 0
0 + 8e = 6 + 10
8e = 6 + 10
Combine like terms: 6 + 10 = 16
8e = 16
Divide each side by '8'.
e = 2
Simplifying
<span>e=2
</span></span>
(sorry, i went into depth)
Answer: C, 9 units
Step-by-step explanation:
(-4, -3) is new point
Answer:
x = -33
Step-by-step explanation:
2/3(x+6)=-18
Multiply each side by 3/2
3/2*2/3(x+6)=-18*3/2
x+6 = -27
Subtract 6 from each side
x+6-6 = -27-6
x = -33